MODELLING OF DISTRIBUTIONS OF CALCULATIVE PARAMETERS FOR HYDROCARBONS RESERVES ESTIMATION APPLYING METHOD OF RANDOM TRIALS - ZHUKOV, M.; DOVZHENKO, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
The method of generation of elective allocation argument not depending from the assumptions of a distribution law is introduced. This method is applicable also at small bulks samples in a task of calculation of hydrocarbons reserves. Is reviewed happen of generation of allocation of argument on the basis of expert rates. The method is intended for the account of the hydrocarbons reserves by a method of casual trials simulation with the indication of the estimation veracity.